PSYCO-ONCOLOGY AS A BRANCH OF THE PSYCOLOGICAL STUDIES - Davtyan , E.L. (Modern Psychology, 2021)
Psycho-Oncology is an interdisciplinary researching and clinical science within the range of Oncology, Psychology and Sociology. It emerged and developed as an oncological separate section, but in recent years it has been developing very fast as a separate scientific field. Psycho-Oncology ensures the cancer patients and their relatives’ psychological welfare and protects patient’s life quality. The aim of this article is to study Psycho-Oncology as a multidisciplinary field, reveal the psychological impulse of the different cancer treatments.